Nutritional Status And Fuctional Status Among Elderly In Santo Yosef Surabaya Nursing Home - Wafi, Afif F; Susilo, Hendro; Nariswari, Angela S (JOURNAL OF WIDYA MEDIKA JUNIOR, 2019)
Introduction: Elderly population is prone to the risk of nutritional status problems. The problem of nutritional status in the elderly will affect their condition, such as functional ability to carry out daily activities. Good nutritional status is an important determinant of functional capacity, independence and quality of life of the elderly. Aim: This research was conducted to find out whether there was a correlation between nutritional status and functional status among elderly in Santo Yosef Surabaya Nursing Home. Methods : This study used an observational analytic study with a cross sectional approach. The sampling technique in this study was purposive sampling. The measuring instrument used was an MMSE questionnaire for assessment of cognitivse function, MNA-SF for assessment of nutritional status and Barthel Index for assessment of functional status. The analysis technique used was the Kendall?s Tau c correlation test. Result : Of the 43 research subjects, 34.9% suffered from malnutrition, 41.9% were at risk of malnutrition, and 23.3% were normal. Functional status data found 2.3% have total dependence, 20.9% heavy dependence, 18.6% moderate dependence, 37.2% mild dependence, and 20.9% are independent. The results demonstrated a significant correlation with the strength of a moderate positive correlation between nutritional status and functional status among elderly in Santo Yosef Surabaya Nursing Home (r = 0.42; p = 0.001). Conclusion: This study shows that there is a significant correlation between nutritional status and functional status.